Down-regulation of 20-HETE Synthesis and Signaling Inhibits Renal Adenocarcinoma Cell Proliferation and Tumor Growth - Alexanian, Anna (2009)
BACKGROUND: We examined the ability of inhibitors of the synthesis or actions of 20-HETE, metabolite of arachidonic acid, to inhibit proliferation of human renal carcinoma cell lines. MATERIALS AND METHODS: 786-O and 769-P cells were exposed to either 10 μM HET0016 (selective inhibitor of 20-HETE synthesis), 10 μM WIT002 (20-HETE antagonist), or vehicle. Subsequently, we assessed the effect of WIT002 on tumor growth in vivo using an ectopic mouse model of clear-cell renal carcinoma. RESULTS: Addition of HET0016 and WIT002 inhibited the proliferation of 786-O and 769-P human renal cell carcinoma lines. HET0016 and WIT002 had little effect on the proliferation of primary cultures of normal human proximal tubule epithelial cells. WIT002 (10 mg/Kg, s.c.) administered daily to athymic nude mice implanted subcutaneously with 786-O cells reduced the growth of the tumors by 84 % compared to vehicle (p<0.001). CONCLUSION: 20-HETE is required for proliferation of human renal epithelial cancers.